Lectora-Based Interactive E-Module: A Solution to Develop Mathematical Logic Intelligence of Islamic Elementary School Student in the Era Society 5.0 - Ulliyah, Himmatul; Sutomo, Moh.; Suhardi, A. Andi (JIP Jurnal Ilmiah PGMI, 2023)
The research designed in this library research aims to describe and analyze the advantages and disadvantages of Lecora-based interactive e-modules in developing mathematical logic intelligence of Madrasah Ibtidaiyah students in the era society 5.0. Data collection techniques using documentation, sourced from Scopus articles totaled 7, International articles totaled 5, Sinta 2 totaled 3, Sinta 3 totaled 6, Sinta 4 totaled 5, Sinta 5 totaled 7, Sinta 6 totaled 1, International Proceedings totaled 2, Google Scholar Journals totaled 4, and Scientific Books totaled 7. After the data is collected then analyzed with descriptive analysis and content analysis. The results showed that the use of Lectora-based interactive e-modules proved effective for developing mathematical logic skills of Madrasah Ibtidaiyah students. And can be offered as an alternative in the world of education to face the era society 5.0 because of the easy access to learning through digital technology or Information and Communication Technology (ICT).